Pengaruh Suasana dan Persepsi Harga Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Di Pomelo Cafe & Resto Kuningan - Intan Nurhayati; Bonifasius MH Nainggolan (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
This research analysis aims to determine the effect of atmosphere and price perceptions on customer satisfaction through purchasing decisions at Pomelo Café & Resto Kuningan. Quantitative method is the method used in research with a sample of 200 respondents who have come to the research site as the final sample size. Questionnaire distribution was carried out by conducting a survey given to customers at Pomelo Cafe. Then data processing is done using Smart-PLS 3 software with the data analysis method used is PLS-SEM. The results of the study show that: (1) atmosphere has a direct and significant impact on purchasing decisions (2) atmosphere has a direct and significant impact on customer satisfaction (3) atmosphere has an indirect impact on customer satisfaction mediated by purchasing decisions (4) Price perception has an impact on purchasing decisions (5) Price perceptions have an impact on customer satisfaction (6) Price perceptions have an indirect impact on customer satisfaction mediated by purchasing decisions (7) Purchase decisions have an effect on customer satisfaction.